TAKDIR DAN RESILIENSI: ANALISIS TAFSIR Q.S. AL-INSYIRAH AYAT 5-6 DAN RELEVANSINYA TERHADAP PEMULIHAN TRAUMA - Zayyadi, Ach.; Masruroh, Wilda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Trauma is an event often associated with significant emotional and psychological pressure, typically caused by unfortunate incidents or experiences related to violence. In recovery, belief in Allah's destiny can empower individuals to accept harsh realities, thereby reducing feelings of frustration and despair. Resilience is understood as the ability to rise from difficulties, strengthened by faith and perseverance. This study discusses the concepts of destiny and resilience in the context of trauma recovery, focusing on the analysis of Q.S. Al-Insyirah verses 5-6 as a foundation. This research employs a thematic approach using library research methods. The study concludes that the Qur'an asserts that every difficulty will be followed by ease, providing hope and motivation. Furthermore, positive thinking is identified as a key to building self-confidence and overcoming trauma, as well as impacting mental health. Through a qualitative approach and integration of Qur'anic exegesis and psychology, this research offers insights into the crucial role of spiritual understanding in the recovery process.